Extraction, isolation and purification of exopolysaccharide from lactic acid bacteria using ethanol precipitation method (Bangladesh Journal of Pharmacology, 2016)
Lactic acid bacteria are classified Generally Recognized As Safe (GRAS) with most effective potential to divert significant amount of fermentable sugars towards the biosynthesis of functional exopolysaccharide. Exopolysaccharides from lactic acid bacteria are receiving a renewed interest due to the claims of human health benefits, such as modulation of immune response system and more importantly in food and pharma industries as a texturizer, viscosifer, emulsifier and syneresis-lowering agent. Its purification methodology involves: a) Extraction of cell-free supernatant from lactic acid bacteria; b) Denature of protein using trichloroacetic acid; c) Ethanol precipitation; d) Dialysis; and e) Freeze drying. However, depending on nature of research, compounds can be further purified using scanning electron microscopy (SEM), infrared spectrum (IR); and nuclear magnetic resonance (NMR) spectral analyses.Video Clips of Methodology:7 min 42 sec   Full Screen   Alternate3 min 36 sec   Full Screen   Alternate